A Successful Non-surgical Management of a Type II Dens Invaginatus with Antimicrobial Photodynamic Therapy: A Case Report: Management of a Type II Dens Invaginatus with PDT - Nasrabadi, Navid; Naseri, Mandana; Khosraviani, Farshad; Nematollahi, Zahra (Iranian Endodontic Journal, 2023)
Endodontic therapy of dens invaginatus (DI) anomalies is challenging due to difficult access, inadequate cleaning and shaping, and incomplete disinfection of its complicated root canal system. The present case report describes the treatment of tooth #10 with tooth discomfort, intermittent pus discharge, and localized swelling. Sinus tract, mobility, and probing grade 1 were observed. The tooth was tender on palpation and percussion with negative responses to pulp sensibility tests. Radiographic assessments revealed an atypical structure of pulpal anatomy, probably dens invaginatus, associated with a large periapical lesion and severe root curvature. Cone-beam computed tomography confirmed the presence of DI type II. Finally, the diagnosis of pulp necrosis with chronic apical abscess of tooth #10 was made. Combining antimicrobial photodynamic therapy as an adjunctive treatment with different irrigation techniques were effective in nonsurgical endodontic management of the complicated DI type II in a maxillary lateral incisor with a large periradicular lesion and severe root curvature. Six-month and one-year recall radiographic images revealed asymptomatic tooth and progressive osseous healing.